Marketing Strategies for a New Academic Economy: Can We Sell French Without Selling Out? - Mary Jean Green (Studies in 20th & 21st Century Literature, 2002)
When I was asked to participate in this discussion, I was told that my comments should reflect in some way the perspective I gained by temporarily crossing the line into academic administration when I became Associate Dean of the Faculty in charge of the Humanities at my home university five years ago, an experience from which I'm still in recovery...
Keywords: perspective; academia; academic administration; Associate Dean of the Faculty; Humanities; university; New Academic Economy; Sell; French